Religious Moderation in Islamic Education: Natural Intra-Religious Student Interactions at MAN 1 Madiun - Lola Ayu Romandonni; Mustaqoril Nurazizah Romadhoni; Ghaitsa Zahira Sofa; Salwa Fawwas Nafiah; Fatimatul Putri Marsyanda; Brenda Shovia Ananta Aprilia Putri; Sofianasoya, Fayyasa; Ardita Dyah Anggraini (Journal of Islamic Education and Intellectual Discourse (JIED), 2025)
Religious moderation at MAN 1 Madiun emphasizes tolerance, respect for differences, and a strong sense of national commitment, in line with Islamic values that prioritize humanity and social harmony. This study was conducted at MAN 1 Madiun because it represents a diverse Islamic educational environment, consisting of students from various religious organizations such as Nahdlatul Ulama (NU) and Muhammadiyah. The purpose of this observation is to understand how religious moderation is implemented among Muslim students with different organizational backgrounds, particularly in daily interactions, worship practices, and attitudes of mutual respect within the school setting. The research applied observation, interviews with an NU-affiliated student, and field notes supported by documentation. The findings reveal that religious activities such as istigasah and collective Qur’an recitation are carried out jointly without organizational distinctions. Although minor differences occur in specific activities—such as the presence or absence of qunut during the dawn prayer—these variations do not lead to conflict but instead reflect diversity within unity. Interactions among students remain harmonious, indicating that MAN 1 Madiun successfully cultivates an inclusive and peaceful learning environment. These findings imply that religious moderation can be practically implemented in educational institutions and serve as a model for strengthening tolerance, unity, and social cohesion among students from different Islamic traditions.